Changes in Leaf Area Index, Leaf Mass Ratio, Net Assimilation Rate, Relative Growth Rate and Specific Leaf Area Two Cultivars of Fig (Ficus carica L.) Treated Under Different Concentrations of Brassinolide - Zulkarnaini, Zulias Mardinata; Sakimin, Siti Zaharah; Mohamed, Mahmud Tengku Muda; Jaafar, Hawa ZE (AGRIVITA, Journal of Agricultural Science, 2019)
There is limited information and insures for next studies on exogenous brassinolide application fig cultivar of Masui Dauphine (MD) and Improved Brown Turkey (IBT). Therefore, the research objective was to determine the impact of concentrations of exogenous brassinolide application on Leaf Area Index (LAI), Leaf Mass Ratio (LMR), Net Assimilation Rate (NAR), Relative Growth Rate (RGR), and Specific Leaf Area (SLA) of fig. Fig resources were propagated using stem cuttings and were transferred into 3:2:1 mixed soil (topsoil:organic matters:sand) media. Two cultivars of fig treated with brassinolide (control, 50, 100 and 200 ml/L) were repeated four times and constructed by Split Plot Randomized Complete Block Design.Â  Changes in the parameter of LAI, LMR, NAR, RGR, and SLA were investigated monthly. There was a significant effect of fig variety alone on LAI, SLA and LMR but it wasnâ€™t affected on NAR and RGR. SLA and LMR were influenced by brassinolide but not on LAI, NAR and RGR. Cultivar IBT showed higher responses to these parameters than cultivar MD after receiving brassinolide treatment. The interaction between brassinolide and variety was significant on LAI, SLA and LMR of fig except in the parameters of NAR and RGR.